2019
DOI: 10.1039/c8ta10964h
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial braided piezo fiber energy harvesters for self-powered wearable technologies

Abstract: A new strategy of a triaxial architecture based on piezoelectric fibers, silver coated nylon and braiding technology as a wearable energy harvesting generator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
95
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 55 publications
2
95
0
1
Order By: Relevance
“…As‐spun PVDF fiber generated a maximum voltage output of 480 mV, while the voltage output of the braided PVDF/BT 10 fiber was found to be 1100 mV. This value is 229% and 250% higher, respectively, than PVDF fiber or previously reported for melt‐spun hybrid PVDF/BT fiber with the same 10 wt% content of BT nanoparticles 49,19. The voltage output of the braided PVDF/BT 20 with more than 10 wt% BT nanoparticles generated a maximum voltage output of 895 mV which is much lower compared to the braided PVDF/BT 10 fiber.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…As‐spun PVDF fiber generated a maximum voltage output of 480 mV, while the voltage output of the braided PVDF/BT 10 fiber was found to be 1100 mV. This value is 229% and 250% higher, respectively, than PVDF fiber or previously reported for melt‐spun hybrid PVDF/BT fiber with the same 10 wt% content of BT nanoparticles 49,19. The voltage output of the braided PVDF/BT 20 with more than 10 wt% BT nanoparticles generated a maximum voltage output of 895 mV which is much lower compared to the braided PVDF/BT 10 fiber.…”
Section: Resultsmentioning
confidence: 54%
“…It was found that the force sensitivity of the textile energy harvesters was 3, 4, and 10 V N −1 for woven, braided, and knitted energy generators, respectively. The results revealed that the knitted energy generators exhibited an almost 6.3‐fold increase in the value (10 V N −1 ) compared to the recent reported 49…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations